Childfree on Hadith Perspective - Nadila, Tika; Mudrika, Syarifah; Ramli, Angraini (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2022)
This study discusses the Childfree phenomenon which is an understanding or lifestyle of being free from having children either biologically or by adopting. This phenomenon had invited pros and cons in society because it was considered incompatible with religion and culture in Indonesia. Based on this phenomenon, in this case the author refers to the thematic theory, phenomenology and hadith syarah to analyze the child-free phenomenon in the perspective of hadith and the views of scholars and uses qualitative research methods as research procedures. This study resulted that the Prophet known to be very supportive of the ummah to have children with the recommendation to marry a woman who can have children, the virtue of praying for children after their parents die and the prophet's prayer to one of his friends so that he can have many children. The law of having children is not mandatory, while responding to this phenomenon is to continue following religious advice as a Muslim by of course still asking the experts, and Childfree perpetrators should not be blasphemed because it is the choice of each individual and it is the right of each individual to decide as what is his way of life.